Volatility and Inequality as Constraints to Shared Prosperity : Paraguay Equity Assessment - World Bank Group (World Bank, Washington, DC, 2014)
Isolated by nature, and recovering from a period of historically low growth during the eighties and nineties, Paraguay faced many economic and social challenges at the beginning of the twenty first century. By year 2000, Paraguay GDP per capita was only 50 percent of the Latin American average and 34 percent of its MERCOSUR partners. High poverty and inequality were an inherent characteristic of the country. Yet, between 2003 and 2013, Paraguay has performed substantially well, seeing a reduction in moderate and extreme (monetary) poverty. This is essentially the result of a period of average significant growth combined with a reduction in inequality. This report explores the factors associated to the observed improvements in welfare and inequality, and investigates the challenges facing their sustainability, given the historical structural problems of Paraguay to maintain growth and improve social indicators. The underlying question is indeed whether the growth model and reduction in inequality are consistent with a positive social dynamics, taking a comprehensive definition of equity, which includes sustainable elimination of absolute poverty, enhancing equality of opportunity and strengthening agency for all groups.